2007
DOI: 10.1007/s10620-006-9124-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Severity of a Mouse Colitis Model with Angiotensin Converting Enzyme Inhibition

Abstract: Ulcerative colitis is characterized by elevated rates of epithelial cell apoptosis, and an up-regulation of pro-apoptotic cytokines including tumor necrosis factor alpha (TNF-α). Recently, angiotensin converting enzyme (ACE) has been shown to promote apoptosis. In addition, pharmacologic ACE inhibition (ACE-I) both prevents apoptosis and reduces TNF-α expression in vitro. We hypothesized that ACE-I, using enalaprilat, would decrease colonic epithelial cell apoptosis and reduce colitis severity in the dextran s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 61 publications
1
60
0
1
Order By: Relevance
“…When wild-type mice were treated with losartan, which blocks AT1 receptor signaling, colonic inflammation was attenuated and colitis ameliorated. This is consistent with a few early studies that reported that an ACE inhibitor ameliorated colonic damage in experimental colitis models2829. Therefore, the endogenous RAS does play a key role in the development of colitis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When wild-type mice were treated with losartan, which blocks AT1 receptor signaling, colonic inflammation was attenuated and colitis ameliorated. This is consistent with a few early studies that reported that an ACE inhibitor ameliorated colonic damage in experimental colitis models2829. Therefore, the endogenous RAS does play a key role in the development of colitis.…”
Section: Discussionsupporting
confidence: 92%
“…Inconsistently, another study showed that serum ACE concentration was reduced in CD and UC patient population27. There are a few reports that show blockade of the RAS with an ACE inhibitor ameliorates colonic damage or colonic fibrosis in experimental colitis models2829, and genetic deletion of AT1 receptor or angiotensinogen gene reduces the severity of colitis in mice212223. Although these studies suggest a role for the RAS in colitogenesis, the underlying mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although angiotensin converting enzymes (ACE) are commonly thought to control blood pressure, the expression of ACE and its associated receptors have been identified within the gastrointestinal mucosa [3], and their abundance has been shown to increase in states of intestinal injury and colitis in both animal models and humans [46]. Thus, ACE may be associated with the pathogenesis of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…OCT preserved sections were snap-frozen in liquid nitrogen and later used for immunofluorescence staining (see PCNA below). The remaining segment was immediately processed for mucosal cell isolation, and RT-PCR as described previously (26). Whole isolated segments were also used for vascularity evaluation.…”
Section: Collection Of Tissuementioning
confidence: 99%
“…cDNA was purified and processed as previously described (26). All primers for selected gene sequences were selected by Primer-BLAST software http://blast.ncbi.nlm.nih.gov/Blast.cgi.…”
Section: Realtime Pcr (Rt-pcr)mentioning
confidence: 99%